Analysis of Lead (Pb) and Zinc (Zn) Heavy Metal Levels in Coastal Waters of Lemukutan Island, Bengkayang Regency - Utami, Naniek Tri; Febriaty, Irma Ramadhani; Munandar, Rizqan Khairan; Santoso, Hendi; Bahri, Samsul (Universitas Teuku Umar, 2025)
The waters of Teluk Surau, Lemukutan Island, Bengkayang Regency are part of a Conservation Area that is the center of economic activities such as pearl shell cultivation, fishing, tourist transportation and settlement. These activities have the potential to pollute waters with heavy metals lead (Pb) and zinc (Zn) which can disrupt ecosystems and public health. This study aims to analyze the concentration of heavy metals Pb and Zn based on location characteristics and human activities in the waters. Sampling was conducted at four strategic points representing residential areas, pearl mussel farms, docks and control areas (no activity). Water samples were taken at a depth of 30 cm, then preserved with HNO₃ until pH ≤ 2 and analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that Pb concentrations ranged from 0.1385-0.1763 mg/L, with the highest concentrations found in residential areas and docks (0.1763 mg/L) and the lowest concentrations in areas without activities (0.1385 mg/L). Zn concentrations ranged from 0.0061-0.0140 mg/L, the highest concentration in the dock area (0.0140 mg/L) and the lowest concentration in the pearl mussel cultivation area (0.0061 mg/L). All sampling locations showed Pb concentrations far exceeded the seawater quality standard for marine tourism (0.005 mg/L) according to Government Regulation No. 22 of 2021 appendix VIII on the Implementation of Environmental Protection and Management, while Zn concentrations were still below the standard.